Jewish Self-Government in Medieval Egypt : The Origins of the Office of the Head of the Jews, ca. 1065-1126 - Cohen, Mark R., 1943- (Book collections on Project MUSE., 1980)
Under three successive Islamic dynasties--the Fatimids, the Ayyubids, and the Mamluks--the Egyptian Office of the Head of the Jews (also known as the Nagid) became the most powerful representative of medieval Jewish autonomy in the Islamic world. To determine the origins of this institution, Mark Cohen concentrates on the complex web of internal and external circumstances during the latter part of the eleventh century.Originally published in 1981.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.